"The sort of design sophistication we were all in need of," Ernst Plischke’s design for Paul’s Book Arcade (1949), Hamilton - Grant, Matt (Architectural History Aotearoa, 2024)
In 1949 a remarkable interior design for a Hamilton bookshop by Ernst Plischke was, according to the client, "the sort of design sophistication we were all in need of." Paul's Book Arcade played a pivotal role in Hamilton social circles in the 1940s, with the owner David Blackwood Paul (aka Blackwood) and his wife Janet Wilkinson, forming their own "centre of human enlightenment." The Blackwood group of friends included painter Margot Phillips, who like Plischke, was a European refugee, painter, critic, and a writer for The Listener, Geoff Fairburn and his wife Jean (also an artist), as well as writer Alexander Gaskell Pickard. Paul's Book Arcade was established in Hamilton in 1901 by Blackwood's father William Henry Paul. In 1933, Blackwood took over the management of the bookshop, reportedly as the result of a disagreement with his father, who by then was a powerful community leader. Paul's local services were a more pressing concern, and so Blackwood inherited what was a "modest emporium" with the atmosphere of a general store. Blackwood would later transform Paul's Book Arcade to such an extent that in 1949 the visiting English publisher Sir Stanley Unwin numbered the bookshop among the fourteen best in the world, and one of the two best in New Zealand. So successful was the bookshop that in 1955 a further two stores were opened, each in Auckland. The first was located on Shortland Street, and the second on High Street, also designed by Plischke. The Blackwood social circle would have a lasting and far‐reaching influence on the mid‐century architecture of Hamilton. Connections with local artists and groups such as the Waikato Society of Arts, allowed a seamless flow of European‐inspired modernist ideals to inform Hamilton's new architecture, interior design, and cultural landscape. The first built manifestation of this movement was the 1949 interior design for Paul's Book Arcade by Austrian architect Ernst Plischke. This presentation will look at the relation between Blackwood and Plischke, the architect's design for the Book Arcade, and how the Blackwood's informed design sensibilities would influence Hamilton's modernist landscape for years afterwards.